Leksikon Perikanan di Danau Diatas - Silvia Nilmayani; Rona Almos; Reniwati Reniwati (Universitas Andalas, 2018)
This paper describes the fisheries lexicon in Lake Diatas Alahan Panjang, Lembah Gumanti, Solok. Also, it explains the meaning of lexicon.Methods and techniques for providing data use the SLC method, note-taking technique, and record technique. Data analysis methods and techniques use basic PUP techniques and HBB techniques. It found 50 words and 21 phrases. The description of the meaning relates to the catching equipment and its parts, supporting equipment, and catches. In general, the cultural meaning of the fisheries lexicon in Lake Diatas is prohibitions. Some of the prohibitions are